2014
DOI: 10.1007/s10933-014-9813-3
|View full text |Cite
|
Sign up to set email alerts
|

Pollen, biomarker and stable isotope evidence of late Quaternary environmental change at Lake McKenzie, southeast Queensland

Abstract: Unravelling links between climate change and vegetation response during the Quaternary is important if the climate-environment interactions of modern systems are to be fully understood. Using a sediment core from Lake McKenzie, Fraser Island, we reconstruct changes in the lake ecosystem and surrounding vegetation over the last ca. 36.9 cal kyr. Evidence is drawn from multiple sources, including pollen, micro-charcoal, biomarker and stable isotope (C and N) analyses, and is used to gain a better understanding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 52 publications
4
36
0
Order By: Relevance
“…Samples were chemically processed following the methods described in Atahan et al (2015) and analysed by alpha spectrometry to determine unsupported 210 Pb activities on 13 subsamples from core LKN1 (0-51.5 cm) and the 42-92 cm LKN2 sequence. A CIC (constant initial concentration) model was used to calculate the ages of the sediment samples (Appleby, 2001).…”
Section: Datingmentioning
confidence: 99%
“…Samples were chemically processed following the methods described in Atahan et al (2015) and analysed by alpha spectrometry to determine unsupported 210 Pb activities on 13 subsamples from core LKN1 (0-51.5 cm) and the 42-92 cm LKN2 sequence. A CIC (constant initial concentration) model was used to calculate the ages of the sediment samples (Appleby, 2001).…”
Section: Datingmentioning
confidence: 99%
“…The discussion by Atahan et al (2015) of the floral species observed in the Lake McKenzie cores lacks the level of detail provided by Donders et al (2006) for Lake Allom, and does not offer any comment on the implications of the variations between species at the sites for palaeoenvironmental reconstructions on Fraser Island on a broader level. An arid period is considered to be the reason for a hiatus in sedimentation from c18300 -14000 cal BP and it is speculated (Atahan et al 2015:152) that the lake became perennially or intermittently dry.…”
Section: Pollen Analysesmentioning
confidence: 99%
“…Atahan et al 2015;Donders et al 2006;Donders et al 2007;Gontz et al 2014;Hembrow et al 2014;Krull et al 2004;Longmore 1997;Longmore and Heijnis 1999;Moss et al 2015;Woltering et al 2014) and North Stradbroke Island (e.g. Barr et al 2013;Boyd 1993;McGowan et al 2008;Mettam et al 2011;Moss et al 2011;Moss et al 2013;Petherick et al 2008aPetherick et al , 2008bPetherick et al , 2011.…”
Section: Palaeoenvironmental Reconstructionsmentioning
confidence: 99%
See 2 more Smart Citations